Victoria H. answered • 08/24/20

Math in plain English

First you need to combine your like terms on the left side of your equation.

-8b -10b - -13 =-5

-8b-10b = -18b so your equation becomes** -18b - -13 = - 5**

now you want to move the 13 to the other side of

the equation. first change the minus a negative into

plus a positive.** -18b + 13 = -5**

Subtract 13 from both sides to change the 13 to a zero

**-18b + 13 - 13 = -5 -13**

now your equation becomes** -18b = -18**

to make -18b into b, divide both sides be -18

**-18b /-18 = -18 / -18**

and your equation becomes** b=1**

Insert 1 back into the original equation wherever you have a b to check.your anawer

**-18(1) -10(1) - -13 = -5**

**-18 - 10 + 13 = -5**

**-5 = -5**

because -5 = -5 is true your answer is correct.

So b = 1